Surveys of African economies : Volume 1, Cameroon, Central African Republic, Chad, Congo (Brazzaville), and Gabon - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1969)
This volume of the Survey of African Economies is devoted to five Equatorial countries of Cameroon, the Central African Republic, Chad, Congo (Brazzaville), and Gabon. The materials contained in this volume are based mainly on published sources, supplemented by data gathered by fund missions from the central banks and national authorities, who have authorized their publication. Since these countries have common economic interests and institutions, much of the information about them lend itself to a general analysis for the region as a whole.
Includes bibliographical footnotes and index.
aia 20/11/2017
Loans
Keywords: Economic history; Central Africa Republic; Economic development; Africa